Investigation of Anthropomorphic Discourses in Biology Textbooks - Dikmenli, Musa; Gülcan, Betül Kamile; Duran, Tuğçe (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2023)
Although anthropomorphic language is known to be widely used in popular science textbooks and in classroom settings by both teachers and students to describe scientific concepts, little is known about how often and for which biology concepts it is used in high school biology textbooks. Since the issue of using anthropomorphic discourses in the language of science is controversial, it is important to analyze such discourses in biology textbooks. This study aimed to analyse the anthropomorphic discourses used in high school biology textbooks. In this study, anthropomorphic discourses used in high school biology textbooks were examined using the document analysis method. The process of analyzing sentences containing anthropomorphism was carried out in five stages: the naming stage; the elimination and separation stage; the compilation and category development stage; the validity and reliability stage; and the stage of digitizing the qualitative data. It was determined that a total of 1074 anthropomorphic discourses were used in relation to 177 biological concepts in the 4 biology textbooks examined. The anthropomorphic discourses in the books were classified into 19 categories. The findings showed that anthropomorphic discourses are used very frequently in high school biology textbooks and most of them are embedded in the language and consist of stereotyped terms and idioms.